Generalized Köthe-Toeplitz duals - I. J. Maddox (International Journal of Mathematics and Mathematical Sciences)
The α and β-duals spaces of generalized ℓp spaces are characterized, where 0<p≤∞. The question of when the α and β dual spaces coincide is also considered.